Ti-6Al-4V Octet-Truss Lattice Structures under Bending Load Conditions: Numerical and Experimental Results - Francesco Di Caprio; Stefania Franchitti; Rosario Borrelli; Costanzo Bellini; Vittorio Di Cocco; Luca Sorrentino (Metals, 2022)
Metal lattice structures produced by means of additive techniques are attracting increasing attention thanks to the high structural efficiency they can offer. In order to achieve the maximum structural performance, numerical design techniques are used almost exclusively, thus based on CAE-FEM codes. Nevertheless, the current manufacturing facilities do not yet guarantee defect-free components, and, therefore, such imperfections need to be introduced in the numerical models too. The present work aims to describe a FE modelling technique for lattice structures based on the use of beam and shell elements, and therefore with a very reduced computational cost. The main structural parameters, such as weight and stiffness and strength, are used to drive the model calibration. Simple mathematical relationships, based on Experimental-CAD-FEM comparisons, are provided to estimate the error related to the numerical model in a simple and fast way. The validation was performed by three-point bending test on flat specimen with regular octet-truss microstructure both with and without external skin. The test articles were produced in Ti6Al4V and by means of the electron beam melting (EBM) technology. The results obtained are in excellent agreement with the experimental ones, indeed the maximum error is about 3%. All this indicates these methodologies as possible tools for evaluating the performance of such kinds of high-tech structures.